OPTIMASI BATERAI ILMIAH TERBARUKAN BERBAHAN DASAR URINE MANUSIA - Permana, Ryan Galih; Wijayanti, Dewi; Jannah, Aunun; Mughny, Aghy Ali (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Have been to be optimized environmentally friendly batteries with the basic ingredients of human urine. Prototyping is done to create a natural energy source of human waste and to overcome the limitations of existing energy sources in Indonesia. The battery is expected to be implemented naturally become pioneers of new energy sources in the future that can be mass produced. Methods of execution in this experiment is dissolving CuCl2 with distilled water. As the battery is used paper media that has been cut to fit the design of the battery. Once the paper is dipped into a solution of CuCl2, then injected human urine and left for a certain time. To determine the presence of voltage on the paper, was measured with a digital Avometer. From the results of measurements that have been made, the value of the maximum voltage of the battery is capable of 616 mV measured in urine composition that has been deposited for 10 days as much as 2 ml and the concentration of a solution of copper (II) chloride by 8 M. With the measured values indicates that the battery that have been made can be implemented as a prototype battery is environmentally friendly natural.Keywords: battery natural, human urine, environmentally friendly